Microbiology and Epidemiology of Infectious Spinal Disease - Jeong, Se-Jin; Choi, Seung-Won; Youm, Jin-Young; Kim, Hyun-Woo; Ha, Ho-Gyun; Yi, Jin-Seok (Journal of Korean Neurosurgical Society, 2014)
Infectious spinal disease is regarded as an infection by a specific organism that affects the vertebral body, intervertebral disc and adjacent perivertebral soft tissue. Its incidence seems to be increasing as a result of larger proportion of the older patients with chronic debilitating disease, the rise of intravenous drug abuser, and the increase in spinal procedure and surgery. In Korea, studies assessing infectious spinal disease are rare and have not been addressed in recent times. The objectives of this study are to describe the epidemiology of all kind of spinal infectious disease and their clinical and microbiological characteristics as well as to assess the diagnostic methodology and the parameters related to the outcomes. A retrospective study was performed in all infectious spinal disease cases presenting from January 2005 to April 2010 to three tertiary teaching hospitals within a city of 1.5 million in Korea. Patient demographics, risk factors, clinical features, and outcomes were assessed. Risk factors entailed the presence of diabetes, chronic renal failure, liver cirrhosis, immunosuppressants, remote infection, underlying malignancy and previous spinal surgery or procedure. We comparatively analyzed the results between the groups of pyogenic and tuberculous spinal infection. SPSS version 14 statistical software was used to perform the analyses of the data. The threshold for statistical significance was established at p<0.05. Ninety-two cases fulfilled the inclusion criteria and were reviewed. Overall, patients of tuberculous spinal infection (TSI) and pyogenic spinal infection (PSI) entailed 20 (21.7%) and 72 (78.3%) cases, respectively. A previous spinal surgery or procedure was the most commonly noted risk factor (39.1%), followed by diabetes (15.2%). The occurrence of both pyogenic and tuberculous spondylitis was predominant in the lumbar spine. Discs are more easily invaded in PSI. At initial presentation, white cell blood count and C-reactive protein levels were higher in PSI compared to TSI (p<0.05). Etiological agents were identified in 53.3%, and the most effective method for identification of etiological agents was tissue culture (50.0%). Staphyococcus aureus was the most commonly isolated infective agent associated with pyogenic spondylitis, followed by E. coli. Surgical treatment was performed in 31.5% of pyogenic spondylitis and in 35.0% of tuberculous spondylitis cases. Many previous studies in Korea usually reported that tuberculous spondylitis is the predominant infection. However, in our study, the number of pyogenic infection was 3 times greater than that of tuberculous spinal disease. Etiological agents were identified in a half of all infectious spinal disease. For better outcomes, we should try to identify the causative microorganism before antibiotic therapy and make every effort to improve the result of culture and biopsy.